An Integrated Photoelectrochemical–Chemical Loop for Solar‐Driven Overall Splitting of Hydrogen Sulfide1. (26th March 2014) - Zong, Xu; Han, Jingfeng; Seger, Brian; Chen, Hongjun; Lu, Gaoqing (Max); Li, Can; Wang, Lianzhou
Abstract Abundant and toxic hydrogen sulfide (H2S) from industry and nature has been traditionally considered a liability. However, it represents a potential resource if valuable H2 and elemental sulfur can be simultaneously extracted through a H2S splitting reaction. Herein a photochemical‐chemical loop linked by redox couples such as Fe2+/Fe3+ and I−/I3− for photoelectrochemical H2 production and H2S chemical absorption redox reactions are reported. Using functionalized Si as photoelectrodes, H2S was successfully split into elemental sulfur and H2 with high stability and selectivity under simulated solar light. This new conceptual design will not only provide a possible route for using solar energy to convert H2S into valuable resources, but also sheds light on some challenging photochemical reactions such as CH4 activation and CO2 reduction.